Evaluation of markers out of the steroid profile for the screening of testosterone misuse. Part I: Transdermal administration. Issue 5 (18th December 2017) - Kotronoulas, Aristotelis; Gomez‐Gómez, Àlex; Fabregat, Andreu; Segura, Jordi; Yang, Sheng; Xing, Yanyi; Moutian, Wu; Marcos, Josep; Joglar, Jesús; Ventura, Rosa; Pozo, Oscar J.
Abstract: Although the introduction by the World Anti‐Doping Agency (WADA) of the steroid module of the athlete biological passport (ABP) marked an important step forward in the screening of testosterone (T) misuse, it still remains one of the most difficult challenges in doping control analysis. The urinary determination of alternative markers has been recently reported as a promising tool for improving the screening of T oral administration. However, their evaluation for other, commonly used, administration routes is still required. The main goal of this study is the evaluation of the potential of 2 groups of metabolites (cysteinyl conjugated and glucuronoconjugated) after transdermal and intramuscular administration of T. Their suitability was evaluated in individuals with both low basal (L‐T/E) and medium basal (M‐T/E) values of T/E. In this Part I, we evaluated the urinary excretion profile of these 2 groups of T metabolites after the administration of 3 doses of T gel to 12 volunteers (6 L‐T/E and 6 M‐T/E) for 3 consecutive days. For this purpose, 9 different concentration ratios (5 cysteinyl conjugated and 4 glucuronoconjugated markers) were studied. Both, the intra‐individual variability and the detection windows (DW) obtained by each ratio were evaluated. Cysteinyl conjugates showed a general low intra‐individual variability and DWs that were shorter than any other tested marker. Despite the relatively large intra‐individual variability, the DWs reached by glucuronoconjugates (2–3 days) were similar to those obtained by markers currently included in the ABP. Overall; this evaluation advises for the introduction of additional glucuronoconjugated markers in the screening of transdermal T administration. Abstract : The screening of testosterone misuse still remains one of the most difficult challenges in doping control analysis. In this study, we evaluated the potential of 2 groups of metabolites (cysteinyl conjugates and resistant glucuronoconjugates) for the detection of transdermal administration of T. Detection windows reached by glucuronoconjugates were similar to those currently obtained, whereas poorer results were obtained with cysteinyl conjugates.